The Variability of Urbanization in Lower Silesian Voivodeship, Poland - DiFranco, Magdalena K. (Wisniewska) (My University, 2012)
Most research studies examining Polish urban patterns at the national scale consider only one approach to quantify changes in the urbanization levels: measurement based on demographic data or measurement based on land-cover. With few exceptions, research on urbanization process utilizing multiple datasets in the individual voivodeships is limited. By applying the urban life cycle model using both demographic data, measured using enumeration units derived from Poland's administrative system, and land-cover data, derived from satellite imagery, this research can have a unique contribution to the Polish urbanization literature. Furthermore, the results of this work also have potential implications for urban planning and management at the provincial level by providing a more comprehensive approach to studying the spatial variation of the urban patterns of communes in a voivodeship. The goal of this research is to characterize the urbanization level of Lower Silesian Voivodeship between 1990 and 2010 using both demographic and land-cover data and apply the urban life cycle model to describe urban change within the province. My hypothesis is that a better understanding of urbanization patterns and trends in the province will result by examining urban change at multiple spatial scales and with multiple data sets. Specifically, I addressed the following research questions to evaluate my hypothesis: 1) what are the patterns and trends of urban change in Lower Silesia at each of the three administrative levels; 2) what is the potential spatial, temporal and typological variability in urbanization patterns within the region based on the two datasets; and 3) how does the inclusion of land-cover information better inform the identification of the stage of the urban life cycle model. Specifically, the urban life cycle model used to categorize the urban development is discussed, and previous urbanization studies in the context of population change as well as land-cover change are reviewed. The Background section introduces the Polish administrative system, which varies considerably from the system in the United States, and describes the study site of Lower Silesian Voivodeship. The Methodology section discusses the analyses needed to address each research question. Specifically, the datasets used in the research are discussed in detail, along with the methods used to quantify urban patterns. The Results of the analysis are then presented. The Discussion section synthesizes the results in order to assess variability of urban change in Lower Silesian Voivodeship at multiple scales and to evaluate the inclusion of land-cover information in the urban life cycle model. Finally, the Conclusion section highlights the major findings of the work.
Includes Tables, Figures, Maps and Bibliography.
Keywords: Lower Silesia; Poland; Urbanization